2014
DOI: 10.18632/oncotarget.2558
|View full text |Cite
|
Sign up to set email alerts
|

Early outcome prediction on 18F-fluorocholine PET/CT in metastatic castration-resistant prostate cancer patients treated with abiraterone

Abstract: Objective: We investigated the role of 18F-fluorocholine positron emission tomography/computed tomography (FCH-PET/CT) in the early evaluation of abiraterone and outcome prediction in patients with metastatic castration-resistant prostate cancer (CRPC).Patient and methods: Forty-three patients with metastatic CRPC progressing after docetaxel received abiraterone 1,000 mg daily with prednisone 5 mg twice daily. Patients were evaluated monthly for serological PSA response and safety. FCH-PET/CT was done at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
80
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 30 publications
0
80
1
Order By: Relevance
“…Moreover, 68 % of the positive scans showed oligometastatic disease. Although it was not an aim of our study, we suggest that using a metabolic radiopharmaceutical, such as choline in castrate-resistant patients could have a role as a predictor of therapy response [32,33]. Indeed, despite the advent of new receptor radiotracers such as 68 Ga-PSMA [34], it seems from a theoretical perspective more appropriate to use a metabolic tracer in the assessment of response to therapy.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, 68 % of the positive scans showed oligometastatic disease. Although it was not an aim of our study, we suggest that using a metabolic radiopharmaceutical, such as choline in castrate-resistant patients could have a role as a predictor of therapy response [32,33]. Indeed, despite the advent of new receptor radiotracers such as 68 Ga-PSMA [34], it seems from a theoretical perspective more appropriate to use a metabolic tracer in the assessment of response to therapy.…”
Section: Discussionmentioning
confidence: 88%
“…Conversely, Breeuwsma et al [23] did not find any significant differences in prostate cancer-specific survival on the basis of 11 C-choline PET/CT results. In our opinion, and by sharing the results by De Giorgi et al [9,10], radiolabelled choline PET, either 11 C or 18 F, might also be useful for monitoring the response to new therapies (such as taxanes or new anti-hormonal agents).Therefore, providing an appropriate support for future clinical trials. This study's limitations are typical for a retrospective study.…”
Section: Discussionmentioning
confidence: 60%
“…De Giorgi et al (19,46) assessed the usefulness of 18 F-choline PET/CT for evaluating the early response to treatment with abiraterone and enzalutamide in mCRPC patients. The authors concluded that a radiologic response, as assessed with 18 F-choline PET/ CT, was associated with more favorable overall survival than a PSA response of greater than or equal to 50% alone.…”
Section: Use Of Choline Pet/ct To Assess Response To Systemic Therapiesmentioning
confidence: 99%
“…In 3 different patient series, 11 C-choline PET/CT led to a change in the decision-making process in approximately 50% of cases (15)(16)(17). Moreover, 11 C-choline PET/CT was recently proposed as a diagnostic tool for monitoring castration-resistant PCa (CRPC) patients treated with chemotherapy (18) and new ADT (19,20). The main drawback of 11 C-choline PET/CT is the relatively low sensitivity in patients with low PSA levels at the time of imaging (13,21,22).…”
mentioning
confidence: 99%